ANALISIS SISTEM PENGGAJIAN KARYAWAN PERUMDA LT KABUPATEN MAGETAN - Ningtias, Yurisa Dwi Aprilia; Trifananta, Stely Aulia; Yusdita, Elana Era (RISTANSI: Riset Akuntansi, 2024)
The research was conducted with the aim of analyzing the employee payroll system at Perumda LT Magetan Regency. The data analysis technique in this research uses descriptive qualitative methods. The data collection method uses interview and documentation techniques. The results of this research conclude that the Perumda LT employee payroll system is running quite well and effectively, but there are weaknesses in manual attendance which is less effective, making it possible for fraud to occur and errors in the employee payroll system.